The use of platelet-rich plasma (PRP) in facial rejuvenation (Research, Society and Development, 2022)
Currently, the search for basic aesthetic procedures, rejuvenation and better self-esteem is on the rise. Platelet-rich plasma (PRP) is a very effective and well-regarded alternative in the aesthetic market, since, as it is a technique that uses the patient's own blood to obtain the product, it reduces the possibility of adverse effects or rejection. Its definition consists of an autologous blood component with a high platelet concentration and growth factor that grants effects on the skin such as the synthesis of new cells and collagen fibers, thus providing natural regeneration, improvement in sagging, wrinkles, blemishes and acne marks. The aim of this study is to gather information about PRP in order to prove its effectiveness in facial rejuvenation through searches on sites such as Google Academic, Scielo and PubMed. It is concluded that there is a need for a greater variety of studies on the subject in order to increasingly improve the technique.